Preventing fraudulent financial reporting with reputational signals of strategic auditors - Sealy, Chezham (Chez) L.; Simon, Chad A. (Contemporary Accounting Research, 2025)
Abstract Financial reporting fraud continues to cost companies millions of dollars annually and is a major source of concern for regulators, stakeholders, and auditors. While academic research has largely focused on external auditors' fraud detection efforts, we analyze whether auditors can help prevent occurrences of fraud through low‐cost reputational signals of higher “strategic reasoning”; strategic reasoning refers to strategies that individuals take in light of the anticipated actions of others (see van der Hoek et al., 2005, A logic for strategic reasoning, AAMAS '05, 157−164). Specifically, we consider the potential impact on manager behavior of signaling whether audit professionals use zero‐, first‐, and second‐order audit approaches. Zero‐order audit approaches involve making decisions based mostly on the auditor's incentives, first‐order approaches involve decisions based mostly on the client's incentives, and second‐ or higher‐order audit approaches involve decisions based on the client's incentives while recognizing that the client will respond to the auditor's decisions (see Wilks & Zimbelman, 2004, Accounting Horizons , 18 (3), 173–184). Using a context‐rich experiment in which manager participants have no history of interacting with the auditor, we find that the likelihood of fraud occurring is lower when it is signaled that audit partners and their teams use a first‐ or second‐order strategic audit approach compared to a zero‐order approach, due to an increase in the perceived likelihood of the auditor detecting fraud. We also consider whether signaling an auditor's level of strategic reasoning influences the level of effort used to conceal fraud and find an increase in the expected level of fraud effort for managers in the first‐ and second‐order audit conditions.